PENERAPAN TERAPI MUROTTAL AL-QUR’AN UNTUK NYERI PASCA OPERASI FRAKTUR FEMUR - Ilva Yulistisia; Idrawati Bahar (CV CENDIKIA JENIUS INDONESIA, 2026)
Femur fracture is a loss of continuity in the femur or thigh bone, femur fracture is divided into two types, namely open femur fracture and closed femur fracture (Mohamad Hidayat, et al, 2021). According to the World Health Organization (WHO) in 2020, states that the incidence of fractures is increasing, noting that there are approximately 13 million people with a prevalence rate of 2.7% (Mardiono et al, 2018). Methods This final paper uses a case report approach. Professional internship practice was carried out from May-June 2023. The population in this Final Paper is all patients with post ORIF femur fractures diagnosed with femur fractures in the trauma center irna surgical room of Dr.M.Djamil Padang Hospital. The evaluation results of the interventions given to patients showed the effect of Qur'anic Murottal therapy on efforts to reduce pain in post ORIF patients in the Trauma Center Irna Surgery room of Dr. M. Djamil Padang Hospital.